Pola Konsumsi Natrium Pada Petani Padi di Kecamatan Gadingrejo - Putri Rahma Azzahra; Diana Mayasari; Intan Kusumaningtyas; Ari Wahyuni (CV. ITTC INDONESIA, 2025)
Excessive sodium intake is widely recognized as a major risk factor for elevated blood pressure and cardiovascular diseases such as stroke and chronic kidney disease. While the human body physiologically requires only around 500 mg of sodium daily, actual consumption levels often exceed the World Health Organization’s (WHO) recommendation of a maximum 2,000 mg per day or 5 grams of table salt. In Indonesia, most sodium intake stems from the frequent use of salt and seasonings in household cooking, rather than from processed foods alone. Rice farmers represent a uniquely vulnerable population due to their physically demanding work and traditional diets that often involve excessive salt and monosodium glutamate use. This study aimed to describe the daily sodium intake patterns among rice farmers in Gadingrejo Subdistrict, Pringsewu, and to identify influencing factors. A cross-sectional descriptive survey was conducted on 102 farmers, using two-day 24-hour food records to estimate sodium intake. Results showed that 36.3% of respondents consumed high levels of sodium (≥ 2,000 mg/day), while 63.7% remained below the WHO threshold. Most participants were aged 45–59 years and had completed only elementary or junior secondary education. Limited nutritional knowledge, cultural cooking norms, and poor access to health education were identified as key contributors to excessive intake. Therefore, implementing context-based nutrition education alongside low-sodium, high-potassium salt substitute (LSSS) policies is strongly recommended to reduce non-communicable disease burden sustainably among rural farmers.